ANALISIS PERHITUNGAN PERSEDIAAN BAHAN BAKU UNTUK MEMPERLANCAR PROSES PRODUKSI PADA PD MIE BERKAH KM 5 PALEMBANG - Hanifati Hanifati; Elisa Elisa; Nadiah Nadiah (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
This research entitled  Analysis of Raw Material Inventory to Expedite the Production Process in PD Mie Berkah which  located at KM 5 Palembang. It is found that the company had some problems in the minimum stock of flour is not optimal and imprecision calculation the number of orders of  raw materials.  It is would like to know the efforts of the company in meeting the production process  in the company. Data collected through field research, interviews,  and observation.  Data from the inventory reports of flour were analyzed by using the formula of Economic Order Quantity  (EOQ) by Handoko (1995)  and Minimal Inventory by Assauri (1999).  This study relevaled that company had been halted due raw materials that have been depleted and  there is no minimum inventory.  It is concluded that the minimum stock of flour the compaany has not been optimal and uncertainty calculations in a number of orders of raw materials. It is sugested that the company make a purchases that  is economical to make it more prifitable for the company.